The Ecofriendly Polybag: Natural Polybag, as an Alternative for Plastic Polybag Problem - Frengki Wijayanto; Muhammad Syarif Khairuddin; Nafis Zahran Alfitra; Naufal Tsaqif; Fikri Irfan Hanafi (Jurnal Integrasi Sains dan Quran, 2022)
Polybags, or seedling containers, are planting media for nurseries, which are usually made of plastic. Plastic polybags have several weaknesses, so recently many organic-based polybags have been developed that are safer and more environmentally friendly. On the other hand, in Indonesia, there is a lot of waste sugarcane, paper, and eggshells that are not used optimally. Bagasse contains cellulose, hemicellulose, and lignin. Paper has wood cellulose fibers. Eggshells have nutrients that are beneficial for plants and contain calcium carbonate (CaCO3) and can be used as a shaper and strengthening for polybags. The combination of these materials, with the addition of tapioca flour as an adhesive, can be used as a substitute for plastic polybags where one of the other advantages of this product can be decomposed in the soil into nutrients for plants. The purpose of this study was to determine the effectiveness of Ecofriendly Polybags and to minimize the use of plastic, as well as efforts to reuse sugarcane, paper, and eggshell waste. This type of research is a qualitative descriptive study where the focus of the description is on making polybag innovations that are safe for the environment. The collection method is through observation, experiment, and literature review. The tests carried out were physical tests, decomposition rate tests, and product trials. The datasets obtained in this study were analyzed using descriptive methods. Based on the tests carried out, this study succeeded in identifying the effectiveness of Ecofriendly Polybags as a polybag innovation that is safe for the environment and as an effort to reuse bagasse, eggshell, and paper waste.